Alternatif Pemecahan Masalah Open Shop Schedulling dengan Pendekatan Algoritma Genetik dan Heuristik - Mochammad Zuliansyah; Giva Andriana Mutiara (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
One of industrial problem is Open Shop Schedulling (OSS). This research try topropose open shop schedulling problem alternative solution with genetic and heuristicapproach. First we try to make a genetic coding for this problem. Machine schedulling systemanalogue as individu, chromosom analogue as a machine (task), and gen analogue as theoperation. Each individu consist of chromosoms, and each chromosom consist of gens. Weused two methods which represented by coding by operation and code task-operation. Afterchromosom coding detected, fitness function can determine the function of givingchromosoms weight to choose parent chromosom and changing population. Fitness functiondesign base on minimum sum of zero time on each machine with high efficiency, and lack ofoverlapping job for each machine.Keywords: open-shop schedulling, genetic algorithm, heuristic, fitness function